HIGH-THROUGHPUT DRUG SCREENING IDENTIFIES HDAC INHIBITORS AS CANDIDATE THERAPEUTICS FOR MYC-DRIVEN MEDULLOBLASTOMA - Wechsler-Reya, Robert J. (Oxford University Press, 2014)
BACKGROUND: Medulloblastoma (MB) is a highly malignant pediatric brain tumor. Despite aggressive therapy, many patients succumb to the disease, and survivors experience severe side effects from treatment. MBs with high levels of the MYC oncogene have a particularly poor prognosis, and would benefit from novel therapies. METHODS: To identify such therapies, we used an animal model of MYC-driven MB for high-throughput drug screening (HTS). RESULTS: Among the most effective compounds identified by HTS were histone deacetylase inhibitors (HDACI). In vitro, HDACI potently inhibited growth of murine and human MYC-driven MB cells, with minimal toxicity to normal cells. In vivo, HDACI significantly slowed growth of MYC-driven tumors, and synergized with PI3-Kinase inhibitors to cause tumor regression. CONCLUSIONS: These studies highlight the value of HTS for identification of effective therapies, and point to HDACI and PI3K inhibitors as promising agents for treatment of aggressive MB. SECONDARY CATEGORY: Preclinical Experimental Therapeutics.